Clinical and genetic analysis of familial neuromyelitis optica spectrum disorder in Chinese: associated with ubiquitin-specific peptidase USP18 gene variants. Issue 12 (1st September 2022) - Chang, Yanyu; Zhou, Luyao; Zhong, Xiaonan; Shi, Ziyan; Sun, Xiaobo; Wang, Yuge; Li, Rui; Long, Youming; Zhou, Hongyu; Quan, Chao; Kermode, Allan G; Yu, Qingfen; et al.
Abstract : Background: Familial clustering of neuromyelitis optica spectrum disorder (NMOSD) was present in Chinese. This study was to investigate the clinical characteristics and genetic background of familial NMOSD. Methods: Through questionnaires in four medical centres in 2016–2020, we identified 10 families with NMOSD aggregation. The statistical differences of clinical characteristics between familial and sporadic NMOSD (22 cases and 459 cases) were summarised. The whole-exome sequencing (WES) for seven families (13 cases and 13 controls) was analysed, compared with our previous WES data for sporadic NMOSD (228 cases and 1 400 controls). The family-based and population-based association and linkage analysis were conducted to identify the pathogenetic genes, the variant impacts were predicted. Results: The familial occurrence was 0.87% in Chinese. Familial patients had higher expanded disability status scale score than sporadic patients (p=0.03). The single-nucleotide polymorphism (SNP) rs2252257 in the promoter and enhancer of ubiquitin-specific peptidase USP18 was linked to familial NMOSD (p=7.8E-05, logarithm of the odds (LOD)=3.1), SNPs rs361553, rs2252257 and rs5746523 were related to sporadic NMOSD (p=1.29E-10, 3.45E-07 and 2.01E-09, respectively). Patients with the SNP rs361553 T/T genotype had higher recurrence rate than C/T or C/C genotype (1.22±0.85 vs 0.69±0.57 and 0.81±0.65, p=0.003 and 0.001, respectively). SNPs rs361553 and rs2252257 altered USP18 expression in brain and nerve tissues. Conclusion: Most clinical characteristics of familial NMOSD were indistinguishable from sporadic NMOSD except for the worst episodes severity. USP18 with impaired intronic regulatory function contributed to the pathogenesis of NMOSD.